Leukocyte Dysregulation and Biochemical Alterations in End-Stage Kidney Disease Patients Under Hemodialysis - Gabriela Goyoneche Linares; Daysi Zulema Diaz-Obregón; Ana Granda Alacote; Michael Bryant Castro Núñez; María Gracia Castañeda Torrico; Alexis Germán Murillo Carrasco; Cesar Liendo Liendo; Katherine Susan Rufasto Goche; Víctor Arrunátegui Correa; Joel de León Delgado (Diseases)
Background: Patients with chronic kidney disease (CKD) exhibit changes in leukocyte dynamics, leading to altered hematological and biochemical parameters and deteriorating kidney function. In this study, we aim to investigate the correlation between leukocyte subpopulations and hematological and biochemical parameters in patients with end-stage CKD undergoing hemodialysis. Methods: This descriptive, analytical, cross-sectional study included 20 end-stage CKD patients on hemodialysis. Leukocyte subpopulations, including classical monocytes (CD14++/CD16−), intermediate monocytes (CD14++/CD16+), non-classical monocytes (CD14+/CD16++), CD4 T lymphocytes (CD3+/CD4+), CD8 T lymphocytes (CD3+/CD8+), B lymphocytes (CD3−/CD19+), NK cells (CD56+/CD16+), and iNKT cells (CD3+/CD56+), were analyzed using flow cytometry. Results: Patients with end-stage CKD on hemodialysis have decreased classical monocytes and increased non-classical monocytes frequency. A positive correlation was observed between non-classical monocytes and total lymphocytes (Rho-Spearman: R = 0.495, p = 0.027) as well as B lymphocytes (R = 0.567, p < 0.05). We discerned the immunological characteristics of diabetic kidney disease (DKD) and CKD due to other causes in this balanced cohort: B lymphocytes negatively correlate with alkaline phosphatase (R = −0.764, p < 0.05), parathyroid hormone (R = −0.929, p < 0.05), and ferritin (R = −0.893, p < 0.05). Additionally, in DKD, non-classical monocytes positively correlate with eosinophils (R = +0.691; p = 0.019) and classic monocytes with neutrophils (R = +0.627, p = 0.039). Meanwhile, a correlation between either total T lymphocytes or helper T lymphocytes and serum albumin was detected on patients with nephropathy due to other causes. Conclusions: CKD alters classical and non-classical monocyte frequency, whilst T and B lymphocyte frequency positively correlates to the proinflammatory non-classical monocytes. In DKD patients, the uremic environment increases classic monocytes, CD16+ inflammatory monocytes, neutrophils, eosinophils, and B lymphocytes. The described leukocyte dynamic correlates with alkaline phosphatase, parathyroid hormone, iron, and serum albumin serological concentration.